E-learning software in the context of Bangladesh : proposal for an interactive model according to bloom's texonomy - Raihan, Ariful Hoque; Shahriyar, Sheikh Sadik (BRAC University, 2010)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2007